2021
DOI: 10.1164/rccm.202007-2854oc
|View full text |Cite
|
Sign up to set email alerts
|

Mast-Cell Tryptase Release Contributes to Disease Progression in Lymphangioleiomyomatosis

Abstract: Author contributions: RB-J, AD, SM, ASN, ZMT, PB and DC performed the experimental work.AD, MCU, DC and STM performed the Affymetrix analysis. IDS performed statistical analysis, SRJ conceived the study, obtained the funding, saw the patients and is guarantor for the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…Our previous analysis of primary LAM-associated fibroblasts exposed in vitro to 621-101 TSC2 À/À cells revealed numerous transcriptional changes (25). Here we identify elevated expression of the epithelial chemokine and mitogen FGF7 in LAFs exposed to 621-101 TSC2 À/À cells and observe expression of FGF7 in LAM lesions.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Our previous analysis of primary LAM-associated fibroblasts exposed in vitro to 621-101 TSC2 À/À cells revealed numerous transcriptional changes (25). Here we identify elevated expression of the epithelial chemokine and mitogen FGF7 in LAFs exposed to 621-101 TSC2 À/À cells and observe expression of FGF7 in LAM lesions.…”
Section: Discussionsupporting
confidence: 49%
“…Previously, we showed that the composition of LAM nodules is heterogeneous, and evolves as lung disease worsens, with tuberin-deficient LAM cells becoming progressively outnumbered by LAM-associated fibroblasts (22). Furthermore, we determined that LAFs cocultured with TSC2 À/À LAM-derived cells underwent significant transcriptional changes, including upregulation of inflammatory cytokines and other growth factors (25). Both Guo et al in LAM-associated AT2 cells relative to cells derived from normal lung using single-cell sequencing.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…LAM cells have biallelic loss-of-function mutations in tuberous sclerosis complex (TSC) 1 or 2, which act to inhibit the mechanistic target of rapamycin complex 1 (mTORC1). LAM cells aberrantly express proteases (predominantly matrix metalloproteinase (MMP) 2 and 9 [ 3 5 ] and cathepsin K (CTSK)), which have collagenolytic activity [ 6 ] and may contribute directly to lung degradation and cyst formation [ 7 9 ]. Consistent with the role of mTORC1 in this disease process, rapamycin is the standard of care for patients with LAM [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the Journal, Babaei-Jadidi and colleagues (pp. 431–444 ) have focused on the tumor microenvironment and identified a critical role for the mast cell in LAM nodule proliferation, adding an important and already targetable mTOR-independent pathway to the LAM armamentarium ( 17 ). The authors beautifully lay out a translational investigation by first identifying increased tryptase positive mast cell presence in LAM nodules, correlating with disease progression.…”
mentioning
confidence: 99%